Persebaran Populasi Aphis craccivora Koch (Homoptera:Aphididae) di Tanaman Kacang Tanah pada Kondisi Air Tanah Tersedia yang Berbeda - Sutikno, Agus (PEST Tropical Journal, 2003)
The objectives of this study were to determine the population density of A .craccivora and its dispersion on groundnut plant under different soil water availabitiles. the study was conducted in a greenhouse of Crop and Horticultural Plant Protection Institute Region III, Palembang since August to November 2001 using corrpletely randomized design with four levels of soil water availabilities and four replications. Each replication consisted of two plants, which were planted on different black, polyvinyl bag. The treatments were 40, 60, 80, and 100% soil water availabitiles The results showed that types of dispersion of A. craccivora on the whole part of groundnut planted on all soil water availabilities tested were similat n, each other. The population was found higher on young leave and bud leave, then followed on leaf stalk, f lower/gynophore, and stem respectively. The differences in the length of leaft trachoma , number of stem trichoma, and water content of leave and stem were the determinant factors, which influenced the population of A. craccivora on leave and stem in the maximum of population density.